KONFLIK KERJA, MOTIFASI KERJA DAN KEPEMIMPINAN TRANFORMASIONAL TERHADAP KINERJA PEGAWAI (STUDI KASUS PADA KANTOR CAMAT LOWOKWARU MALANG) - Bagus Alisyah Putra; Abdul Kodir Djaelani; M. Khoirul ABS (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACTThe purpose of this study is to understand the influence of work conflict, motivation, and transformational leadership on the performance of the employee at Kantor Camat Lowokwaru Malang. The population in this study were 33 with the same number of samples. This study used an explanatory research type with a quantitative approach. Primary data was measured using a questionnaire and analyzed using a SPSS 14.0. The result shows that both work-conflict and transformational leadership significantly influenced to work performances. On the other hand, motivation doesn't have any influences on work performance. However, altogether those three variables significantly influenced to work performances. Keywords : Work Conflict, Work Motivation, Transformational Leadership and Work Perfomance.